Spectroscopic and electrochemical studies of high-valent water soluble manganese porphyrine. Electrocatalytic water oxidation - Luna, Maria Alejandra (2014)
We report herein the catalytic oxidation of water to molecular oxygen with water-soluble 5,10,15,20-tetra(N-methylpyridyl) porphyrinato manganese (III) chloride, [PMn(III)]Cl5. The homogeneous chemical and electrochemical oxidation of [PMn(III)]Cl5 was studied in aqueous buffer solution by UV-vis and cyclic voltammetry techniques. Firstly, [PMn(III)]Cl5 was characterized by spectroscopy in pH 7 and 10, measuring the changes produced by oxidation with a chemical agent. These studies showed that intermediates with higher oxidation states, [PMn(IV) = O]Cl4 and [PMn(V) = O]Cl5, are formed under these conditions and they are more stable at pH 10 at room temperature. The same result was obtained by electrochemical oxidation. The electrochemical studies showed that [PMn(III)]Cl5 is adsorbed on glassy carbon electrode surface. However, this does not help explain the high oxidation current obtained in both pHs at high anodic potentials. We demonstrated that these currents, in the cyclic voltammperogram of the [PMn(III)]Cl5, are due mainly to the water catalytic oxidation by the [PMn(V) = O]+5 intermediate. Besides, we show that chloride ion present in the porphyrin structure can also be oxidized by the same mechanism.